Aprendiendo desde el jardín: ciudadanía global y paisaje en el primer jardín botánico de San Martín de Porres, Lima, Perú - Miranda Rodrigo, Letzy Rubi (2025)
This essay aims to propose a reflection on the potential of a citizen-led intervention in San Martín de Porres, Metropolitan Lima, as a formative space for global citizenship. The intervention took place in a neighborhood of the district through the creation, in 2018, of a botanical garden with wide botanical and biological diversity. The main motivation behind this initiative was to create a space for children in the area to engage with nature, fostering greater sensitivity and responsibility in the face of climate challenge. Currently, the garden has hosted school excursions from two local schools. The Swiss Commission for UNESCO recognizes the potential of education in non-formal and informal settings for the development of global citizenship. In this sense, we analyze the potential of the botanical garden as a non-formal learning environment, drawing on the method proposed by its creator: a multisensory approach to addressing complexity. The starting point is the space itself —that is, the landscape— experienced through all the senses and through an understanding of the systems and relationships that converge within it. In this way, the landscape becomes a space for citizenship education. Understanding landscape not as an exceptional place but as an everyday, immediate, and proximate one allows us to focus on the role of its inhabitants. The everyday landscape is the first step in our relationship with the portion of the world we live in, the first scale from which we recognize ourselves within broader national or global scales. Recognizing ourselves as actors means acknowledging our potential as citizens, developing a sense of responsibility and care for our surroundings, and imagining new landscapes.